Reformulation Of Punishment Objectives In The National Criminal Code: A Restorative Justice Perspective - Yohanes Pande; Bustomi; Eko Budi Sariyono; Ade Ari Gumilar; Stelvia W. Noya (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
This article examines the reformulation of sentencing objectives under the Indonesian National Criminal Code as regulated in Law Number 1 of 2023 by positioning restorative justice as its central analytical framework. The enactment of the new Criminal Code represents a response to long-standing critiques of the conventional punitive paradigm, which has largely been dominated by retributive and retaliatory approaches. Such a model is considered insufficient in addressing the needs of victims, restoring disrupted social relations, and promoting the rehabilitation of offenders. Consequently, the integration of restorative justice values into the objectives of sentencing constitutes a strategic effort to establish a more humane and equitable criminal justice system. This study employs a normative juridical method with statutory and conceptual approaches. The analysis focuses on provisions governing sentencing objectives within the National Criminal Code and evaluates their alignment with the principles of restorative justice as developed in contemporary criminal law discourse. Data were collected through library research, encompassing legislation, legal doctrines, and national scholarly journal articles addressing criminal law reform and restorative justice. The findings indicate that the National Criminal Code has incorporated a significant shift in sentencing objectives, moving beyond punishment-oriented models toward victim recovery, offender rehabilitation, and the preservation of social balance and harmony. Nevertheless, the practical implementation of restorative justice based sentencing objectives continues to face substantial challenges, particularly with regard to the readiness of law enforcement authorities, prevailing legal culture, and the need for more detailed and operational implementing regulations. Therefore, the reformulation of sentencing objectives within the National Criminal Code requires strengthened implementation policies to ensure that restorative justice principles are effectively realized in criminal justice practice.